Analyzing of Taboo Language in The Script of 'Uncut Gems' Film by Safdie & Bronstein - Daulay, Sholihatul Hamidah; Dimas; Alvindi (JLE: Journal of Literate of English Education Study Program, 2024)
This research examines the use of taboo language in the film Uncut Gems, focusing on identifying the types of taboo language and their functions. Using a descriptive qualitative approach, the study analyzes linguistic features within the film. The findings reveal four types of taboo language: vulgarity (69 occurrences, 61%), epithet (30 occurrences, 26%), obscenity (12 occurrences, 10%), and profanity (3 occurrences, 3%). Each type serves distinct functions in the narrative, including being provocative, showing contempt, drawing attention, and mocking authority. The most frequent function was provocation (65 occurrences, 61%), followed by showing contempt (23 occurrences, 21%), drawing attention (19 occurrences, 17%), and mocking authority (1 occurrence, 1%). Taboo language plays a crucial role in intensifying the film's emotional impact and enhancing the portrayal of complex social dynamics. This study contributes to understanding how language in film serves as a tool for narrative depth and audience engagement, offering insights into the interplay between language, story, and social context in cinema.